The Need for Head Protection Protocols for Craniectomy Patients during Rest, Transfers and Turning - Pandit, Anand S.; Singhal, Prabhav; Khawari, Sogha; Luoma, Astri M. V.; Ajina, Sara; Toma, Ahmed K. (Frontiers in Surgery, 2022)
After craniectomy, patients are generally advised to wear a helmet when mobilising to protect the unshielded brain from damage. However, there exists limited guidance regarding head protection for patients at rest and when being transferred or turned. Here, we emphasise the need for such protocols and utilise evidence from several sources to affirm our viewpoint. A literature search was first performed using MEDLINE and EMBASE, looking for published material relating to head protection for patients post-craniectomy during rest, transfer or turning. No articles were identified using a wide-ranging search strategy. Next, we surveyed and interviewed staff and patients from our neurosurgical centre to ascertain how often their craniectomy site was exposed to external pressure and the precautions taken to prevent this. 59% of patients admitted resting in contact with the craniectomy site, in agreement with the observations of 67% of staff. In 63% of these patients, this occurred on a daily basis and for some, was associated with symptoms suggestive of raised intracranial pressure. 44% of staff did not use a method to prevent craniectomy site contact while 65% utilised no additional precautions during transfer or turning. 63% of patients received no information about avoiding craniectomy site contact upon discharge, and almost all surveyed wished for resting head protection if it were available. We argue that pragmatic guidelines are needed and that our results support this perspective. As such, we offer a simple, practical protocol which can be adopted and iteratively improved as further evidence becomes available in this area.